2011
DOI: 10.1111/j.1751-1097.2011.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fungicidal Photodynamic Effect of Hypericin on Candida Species

Abstract: Hypericin is a natural photosensitizer considered for the new generation of photodynamic therapy (PDT) drugs. The aim of this study was to evaluate the in vitro fungicidal effect of hypericin PDT on various Candida spp., assessing its photocytotoxicity to keratinocytes (HaCaT) and dermal fibroblasts (hNDF) to determine possible side effects. A 3 log fungicidal effect was observed at 0.5 McFarland for two Candida albicans strains, Candida parapsilosis and Candida krusei with hypericin concentrations of 0.625, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 48 publications
5
37
0
Order By: Relevance
“…In line with this view, differential sensitivity to PDT in vitro has been described for other yeast species, such as Candida. 7 In most patients, we observed a decrease in the number of Malassezia colonies in the control area after exposure to red light illumination, in agreement with previous reports describing the inhibitory effects of a red light-emitting diode on the growth of bacteria and yeast. 8 There are 2 main limitations to our study.…”
supporting
confidence: 91%
“…In line with this view, differential sensitivity to PDT in vitro has been described for other yeast species, such as Candida. 7 In most patients, we observed a decrease in the number of Malassezia colonies in the control area after exposure to red light illumination, in agreement with previous reports describing the inhibitory effects of a red light-emitting diode on the growth of bacteria and yeast. 8 There are 2 main limitations to our study.…”
supporting
confidence: 91%
“…A previous study demonstrated that, with hypericin, an anthraquinone dye, the incubation time had no influence on photoinactivation of C. albicans [21], but too brief of an exposure might lead to the incomplete incorporation of the photosensitizer in microorganisms. The practical application time of the photosensitizer needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The oral cavity sustains more than 700 species of microorganisms, few of which participate in the pathogenesis of various oral diseases, such as dental caries and candidiasis [35,36]. The main challenge regarding the treatment of these diseases resides in antimicrobial resistance, reoccurrence (treatment fail), interactions with other medical regimens, organ toxicity, staining potential, taste alteration, and compliance of the patients to achieve therapy success [36].…”
Section: Photodynamic Antimicrobial Chemotherapy In Dentistrymentioning
confidence: 99%
“…The main challenge regarding the treatment of these diseases resides in antimicrobial resistance, reoccurrence (treatment fail), interactions with other medical regimens, organ toxicity, staining potential, taste alteration, and compliance of the patients to achieve therapy success [36].…”
Section: Photodynamic Antimicrobial Chemotherapy In Dentistrymentioning
confidence: 99%